2021
DOI: 10.1038/s41419-021-03616-9
|View full text |Cite
|
Sign up to set email alerts
|

Ceramides and sphingosine-1-phosphate mediate the distinct effects of M1/M2-macrophage infusion on liver recovery after hepatectomy

Abstract: Post-hepatectomy liver dysfunction is a life-threatening morbidity that lacks efficient therapy. Bioactive lipids involved in macrophage polarization crucially regulate tissue injury and regeneration. Herein, we investigate the key bioactive lipids that mediate the cytotherapeutic potential of polarized-macrophage for post-hepatectomy liver dysfunction. Untargeted lipidomics identified elevation of ceramide (CER) metabolites as signature lipid species relevant to M1/M2 polarization in mouse bone-marrow-derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 50 publications
3
16
0
Order By: Relevance
“…[ 29 ] In addition, LR and recovery of liver function are accelerated significantly when reparative bone‐marrow–derived macrophages (BMDMs) are infused into hepatectomized mice. [ 13 ] However, the underlying mechanism in which reparative macrophages affected LR were not clearly shown. Our study showed that increased proportion of reparative Ly6C lo and subsequent HGF production may contribute to an advanced proliferation peak after major hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 29 ] In addition, LR and recovery of liver function are accelerated significantly when reparative bone‐marrow–derived macrophages (BMDMs) are infused into hepatectomized mice. [ 13 ] However, the underlying mechanism in which reparative macrophages affected LR were not clearly shown. Our study showed that increased proportion of reparative Ly6C lo and subsequent HGF production may contribute to an advanced proliferation peak after major hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 , 12 ] Recent studies have shown that the cytokines produced by polarized macrophages may regulate liver repair and regeneration after hepatectomy. [ 13 , 14 ] However, the specific roles of Ly6C lo and Ly6C hi macrophages and their secreted cytokines in LR remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The results of these studies illustrated that an established primary culture model for macrophage subtypes (BMDM) [45][46][47][48] exhibited inconsistent expression of the M2 surface marker, SR-A. [6][7][8]46 There was no signicant difference in uptake of SDIO, which is targeted to SR-A, between polarized phenotypes in BMDMs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, untargeted lipidomic analysis conducted in mouse BM-derived macrophages (BMDM) identified signature lipid species relevant to the M1/M2 polarization. While M1 BMDMs expressed a ceramide-generation metabolic pattern, leading to elevation of ceramide, M2 BMDMs expressed a ceramide-breakdown-metabolic pattern, resulting in upregulation of S1P ( 112 ).…”
Section: Bm Microenvironment Cellular Components Release Sphingolipid...mentioning
confidence: 99%